Differences in cerebral and muscle oxygenation patterns during exercise in children with univentricular heart after Fontan operation compared to healthy peers. (1st September 2019) - Vandekerckhove, Kristof; Coomans, Ilse; Moerman, Annelies; Panzer, Joseph; De Groote, Katya; De Wilde, Hans; Bove, Thierry; François, Katrien; De Wolf, Daniel; Boone, Jan
Abstract: Background: We assess whether the lower exercise tolerance in children with univentricular heart (UVH) after Fontan operation is associated with altered peripheral muscular and cerebral tissue oxygenation. Methods: 18 children with UVH and 20 healthy subjects performed an incremental ramp exercise test. Changes in the cerebral and muscular pattern of oxygenated (O2 Hb) and deoxygenated hemoglobin (HHb) and local tissue oxygenation (TOI) were analyzed by means of Near Infrared Spectroscopy (NIRS). Correlations between arterial saturation during exercise and tissue oxygenation were evaluated. Results: In UVH, maximal oxygen consumption (VO2 peak/kg, 28.9 ± 7.9 vs. 46.3 ± 11.9 ml/min/kg, P < 0.001), heart rate (HRpeak, 168 ± 13 vs. 193 ± 12 bpm, P < 0.001) and load (Ppeak, 73 ± 19 vs. 133 ± 68 W, P < 0.001) were lower, VE/VCO2 slope was higher (34.5 ± 5.9 vs. 27.1 ± 3.9, P < 0.001). A faster and steeper course up to the same level of HHb and absent increase in O2 Hb was seen at cerebral level in UVH; tissue oxygenation index (TOI) demonstrated a steady decrease from the start of exercise. At the muscular level, HHb curve has a similar pattern compared to controls, with an early cessation. O2 Hb has a similar pattern, but with early discontinuation at a higher O2 Hb-level. Muscular TOI has the same course throughout exercise, starting from a lower level. Lower arterial saturation and higher age correlated with lower VO2 peak; higher amplitude of muscular TOI and lower amplitude cerebral TOI correlated with higher VO2 peak. Conclusion: Children after Fontan procedure have different oxygenation mechanisms at muscular and cerebral level. This reflects a different balance between O2 supply to O2 demand which might contribute to the reduced exercise tolerance in this patient population. Highlights: Children after Fontan operation have lower exercise performance compared to healthy peers. Cerebral and muscular oxygenation patterns during exercise are different in UVH. There are arguments towards an important role of impaired cerebral oxygenation in the cause of exercise limitation. Local oxygenation patterns are related with maximal oxygen consumption during exercise.